Intersectoral Action For Addressing Social Determinants Of Health: Policy Integration Across Health, Education, And Social Protection - Bambang Wahrudin; Mochammmad Syafiuddin Shobirin (International Journal of Health Systems and Policy, 2025)
Persistent health inequities across Latin America are deeply rooted in structural social determinants, including poverty, unequal access to education, and inadequate social protection systems. This study investigates how intersectoral policy integration has been employed as a strategic response to these challenges, focusing on the alignment of health, education, and social protection policies within national frameworks. Utilizing a comparative case study approach, the research analyzes intersectoral strategies implemented in Brazil, Colombia, and Peru. These countries were selected based on the existence of national SDH policies, availability of data, and documented outcomes in health equity. The analysis draws from government policy documents, international reports, and academic literature, and applies the “Health in All Policies” (HiAP) framework as an analytical lens. The findings indicate that interministerial coordination, high-level political commitment, and flexible local implementation are critical to success. Brazil’s integration of health and cash transfer programs, Colombia’s territorial equity planning, and Peru’s centralized coordination through MIDIS illustrate diverse but effective models. Despite measurable progress, challenges remain, including fragmented information systems, uneven institutional capacity, and political instability. The study concludes that sustained, equity-focused governance is essential for effective intersectoral action and that Latin America’s experiences offer valuable lessons for global public health policy and development planning.